Efektivitas Ekstrak Pektin dari Kulit Buah Jeruk Bali (Citrus maxima) Sebagai Antimikroba - Wana, Nur; Pagarra, Halifah (Fakultas MIPA UNM, 2018)
Abstract. The aim of this study was to investigate the effectiveness of pectin extract and antimicrobial activity of pectin extract from the skin of grapefruit (Citrus maxima) with variations in pH, temperature, and extraction time. This study was an experimental study with laboratory testing using a completely randomized design (CRD) with 2x3x3 factorial three times repetition. Factor A is pH: 1.5 (A1), 2.5 (A2). Factor B is the heating temperature: 60°C (B1), 80°C (B2), 100oC (B3). Factor C is time: 60 minutes (C1), 90 minutes (C2), 120 minutes (C3). While the design measurement of antimicrobial activity is carried out by calculating the diameter of the inhibition zone (mm). All data obtained were analyzed using ANOVA (α = 0.05%, then continued by Tuckey's advanced test using SPSS). Extraction of pectin from the skin of grapefruit using a conventional method with hydrochloric acid (0.5N HCl). The extraction process was carried out by heating the hot plate by varying the temperature (60 oC; 80 oC; 100oC), pH (1.5; 2.5), and extraction time (60; 90; 120 minutes). Significant pectin yields obtained were tested for antimicrobial activity and measured inhibitory zones produced based on the diameter of the antimicrobial area. The results showed that extraction was influenced by pH, temperature, and extraction time and the highest pectin yield was obtained by extraction with ph 2.5, temperature 60oC, time 90 minutes as much as 27.8%. While the antimicrobial activity of pectin extract from the skin of grapefruit (Citrus maxima) has antibacterial activity because it can inhibit the growth of Escherichia coli bacteria, Staphylococcus aureus. However, it has no antifungal activity against Candida albicans.Keywords: Grapefruit skin (Citrus axima), Pectin, extraction, antimicrobial activity.